2011
DOI: 10.1108/02686901111151332
|View full text |Cite
|
Sign up to set email alerts
|

The internal audit function

Abstract: PurposeThe purpose of this paper is to provide insights into the current roles and responsibilities of the internal audit (IA) function and the factors perceived to be necessary to ensure its effectiveness. The current performance evaluation practices of IA are also examined.Design/methodology/approachSemi‐structured interviews were utilised to elicit the perceptions of key corporate governance actors about the evolving role of IA, as well as IA effectiveness, in terms of its design, measurement and evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
102
1
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(127 citation statements)
references
References 30 publications
11
102
1
13
Order By: Relevance
“…Moreover, this paper tries to explain stakeholders' perceptions on internal audit effectiveness using measures such as competency of internal auditors, the size of internal audit department, relationships between internal auditors and external auditors, and the level of management support for internal audit performance. These factors are identified based on a review of previous studies (see Alzeban & Sawan, 2013;Soh & Bennie, 2011;Ahmad et al, 2009;Mihret & Yiamaw, 2007;Ali et al, 2007;Sarens & Beelde, 2006;Carcello et al, 2005;Brierley et al, 2001Brierley et al, , 2003, along with studying the performance of internal audit departments, guidelines on the international standards for the Professional Practice of Internal Auditing (ISPPIA) published by the international institution for internal audit (IIA), and other available documents and evidence. Drogalas et al (2015) study investigates the specific factors associated with internal audit effectiveness in the Greek business environment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this paper tries to explain stakeholders' perceptions on internal audit effectiveness using measures such as competency of internal auditors, the size of internal audit department, relationships between internal auditors and external auditors, and the level of management support for internal audit performance. These factors are identified based on a review of previous studies (see Alzeban & Sawan, 2013;Soh & Bennie, 2011;Ahmad et al, 2009;Mihret & Yiamaw, 2007;Ali et al, 2007;Sarens & Beelde, 2006;Carcello et al, 2005;Brierley et al, 2001Brierley et al, , 2003, along with studying the performance of internal audit departments, guidelines on the international standards for the Professional Practice of Internal Auditing (ISPPIA) published by the international institution for internal audit (IIA), and other available documents and evidence. Drogalas et al (2015) study investigates the specific factors associated with internal audit effectiveness in the Greek business environment.…”
Section: Introductionmentioning
confidence: 99%
“…This second group of studies argues that the roles of internal audit are complex and constantly evolving (Soh and Martinov‐Bennie, ) and therefore cannot be confined to governance oversight. A host of contrasting viewpoints regarding the roles of internal audit is offered.…”
Section: The Multiple Roles Of Internal Auditmentioning
confidence: 99%
“…The IIA has failed to offer a way out of this impasse, even compounding the problem by recently amending its standards to allow internal auditors to assume other responsibilities (in addition to assurance and consulting activities), according to the needs of the organization (Institute of Internal Auditors, ).While the IAF's roles may have been uncertain before this amendment, they are even more nebulous now. They must be more clearly defined or the confusion will ultimately affect (i) the practice of internal audit and (ii) IAF quality assessment by practitioners (and researchers) (Roussy and Brivot, ; Soh and Martinov‐Bennie, ). Consequently, this important research avenue remains wide open.…”
Section: The Multiple Roles Of Internal Auditmentioning
confidence: 99%
“…The audit expectation gap is primarily concerned with the existence of differences in perceptions between the audit profession and the public regarding the nature, purpose and functions of those who engage in audit activities (Soh & Martinov-Bennie, 2011;Bedard, Sutton, Arnold & Phillips, 2012). A study by McEnroe and Martens (2001) found that investors have higher expectations for the various components of assurances of the audit-process than do auditors.…”
Section: Audit Expectation Gapmentioning
confidence: 99%
“…Whilst internal auditing evaluates an organization"s operations by personnel within the same organization (Almström & Kinnander, 2011), external audit is the independent examination and expression of an opinion on the financial statements of an entity and risk therein by external professionals (Bediako-Ahoto, 2011). According to Soh and Martinov-Bennie (2011) the processes of external audit forms a smaller part of the audit process and therefore investors and other stakeholders often depend on the work of other organizational constituents when making decision regarding a particular organization (Chatterjee, Tooley, Fatseas & Brown, 2011). further increased the scope of auditing functions in organizations (Bishop, DeZoort & Hermanson, 2017). This is clearly evidenced by the growing corporate governance literature in financial control and auditing (Carcello, Hermanson & Ye, 2011).…”
Section: Introductionmentioning
confidence: 99%